2010
DOI: 10.1002/dc.21489
|View full text |Cite
|
Sign up to set email alerts
|

Cytological differential diagnosis among adenocarcinoma, epithelial mesothelioma, and reactive mesothelial cells in serous effusions by immunocytochemistry

Abstract: The objective of the study is to estimate the expression of some antibodies in the metastatic adenocarcinomas, malignant epithelial mesotheliomas, and reactive mesothelial cells in serous effusions and to choose effective panel to the differential diagnosis. Totally 113 effusion cytology samples (80 pleural fluid, 30 ascitic, and 3 pericardial fluid) from 60 cases of metastatic adenocarcinoma (ACA), 18 cases of malignant epithelial mesothelioma (MM), and 35 cases of reactive mesothelium (RM) were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 29 publications
(29 reference statements)
5
97
0
Order By: Relevance
“…65 Immunohistochemical markers used on histological samples to differentiate between benign and malignant mesothelial proliferation have also been used in cytology with similar unsatisfactory results. [28][29][30][31][32][33][34][35][36] The present study shows that the BAP1 profile of mesothelial cells is also easily identifiable on effusions and cell blocks. Benign mesothelial cells were invariably positive for BAP1, whereas 64% of mesotheliomas showed loss of protein; in equivocal cases by morphology, BAP1 negativity on mesothelial cells had a 100% positive predictive value for the diagnosis of mesothelioma: all six samples containing mesothelial cells negative for BAP1 were associated with a histological diagnosis of BAP1-negative mesothelioma.…”
Section: Discussionsupporting
confidence: 60%
“…65 Immunohistochemical markers used on histological samples to differentiate between benign and malignant mesothelial proliferation have also been used in cytology with similar unsatisfactory results. [28][29][30][31][32][33][34][35][36] The present study shows that the BAP1 profile of mesothelial cells is also easily identifiable on effusions and cell blocks. Benign mesothelial cells were invariably positive for BAP1, whereas 64% of mesotheliomas showed loss of protein; in equivocal cases by morphology, BAP1 negativity on mesothelial cells had a 100% positive predictive value for the diagnosis of mesothelioma: all six samples containing mesothelial cells negative for BAP1 were associated with a histological diagnosis of BAP1-negative mesothelioma.…”
Section: Discussionsupporting
confidence: 60%
“…In those studies, MOC-31 was part of a panel of immunohistochemical stains. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In the current study, the sensitivity (87%) and specificity (100%) of MOC-31 alone in the detection of metastatic adenocarcinoma in effusion cytology specimens was within the range of sensitivities (76%-100%) and specificities (92%-100%) reported for antibody panels that included MOC-31.…”
Section: -3mentioning
confidence: 51%
“…The antibodies currently available for differentiation in effusion specimens include antibodies that recognize cells of mesothelial origin (such as calretinin, D2-40, cytokeratin [CK] 5/6, Wilms' tumor-1 [WT-1], and mesothelin) and antibodies that recognize adenocarcinomas (such as MOC-31, carcinoembryonic antigen [CEA], B72.3, and Ber-Ep4). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The majority of studies demonstrating the usefulness of these markers have used panels comprised of different combinations of the antibodies for mesothelial cells/mesothelioma and adenocarcinomas from different primary tumor sites.…”
mentioning
confidence: 99%
“…Cotton block method is another alternative by which cytomorphological features in body fluids can be studied. 11,[15][16][17] In this study, all three malignancies found in the smears and blocks were adenocarcinomas. This comprised 8.1 % of cases (3/37).…”
mentioning
confidence: 48%